The role of the quality of educational services and the discipline of Buddhist education teachers affects student learning outcomes - Elisabet Tansel; Suherman Suherman; Khie Khiong (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
Student learning outcomes of those who participate in learning activities at school certainly expect maximum learning outcomes, therefore the quality of educational services and discipline must be considered in determining student learning outcomes.This study aims to determine the effect of the quality of educational services and the discipline of Buddhist education teachers on the learning outcomes of Putra Bangsa Berbudi Junior High School students in the school period year 2021/2022. This study uses a saturated sampling technique by taking the entire population as a sample with a study consisting 42 Buddhist junior high school students. This research design uses a quantitative approach with descriptive statistical data analysis techniques. The instrument for collecting data was a closed questionnaire distributed through a questionnaire sheet, the results of the questionnaire were tested through instrument testing, classical assumptions, and simple and multiple regression correlation analysis. Based on the results of data analysis using a simple linear regression formula, the magnitude of Adjusted R coefficient of determination is 0.734, which means that the quality of educational services and the discipline of Buddhist education teachers effects on student learning outcomes is 73.4% and the remaining 26.6% is explained by the influence of other factors not discussed in this study. Based on the results of this study, it can be concluded that student learning outcomes can be improved through the quality of educational services and the discipline of Buddhist education teachers, either partially or simultaneously. Keywords: Quality of Educational Services; Discipline of Buddhist Education Teachers; student learning outcomes